Mutations in IRX5 impair craniofacial development and germ cell migration via SDF1 - GÜRAN, TÜLAY (NATURE PUBLISHING GROUP, 2012)
Using homozygosity mapping and locus resequencing, we found that alterations in the homeodomain of the IRX5 transcription factor cause a recessive congenital disorder affecting face, brain, blood, heart, bone and gonad development. We found through in vivo modeling in Xenopus laevis embryos that Irx5 modulates the migration of progenitor cell populations in branchial arches and gonads by repressing Sdf1. We further found that transcriptional control by Irx5 is modulated by direct protein-protein interaction with two GATA zinc-finger proteins, GATA3 and TRPS1; disruptions of these proteins also cause craniofacial dysmorphisms. Our findings suggest that IRX proteins integrate combinatorial transcriptional inputs to regulate key signaling molecules involved in the ontogeny of multiple organs during embryogenesis and homeostasis.
Keywords: NEURAL CREST; GENE; PROTEIN